Pengaruh Problem Based Learning Dan Motivasi Berprestasi Terhadap Kemampuan Pemecahan Masalah - Miftahus Surur; Tartilla Tartilla (ILIN Institute Makassar, 2019)
This study aims to examine students' problem solving abilities in mathematics with different achievement motivation between those taught through problem based learning and discussion. The design of this study uses quasi-experimental forms of Non-equivalent Control Group Design. The experimental group from this study was given PBL treatment, while the control group was treated with the discussion method. The data of this study were analyzed by the Univariate Analysis of Variance technique. The results showed that (1) there was a significant effect between PBL models and discussion models on students 'problem solving abilities, (2) there was a significant effect between students with high and low achievement motivation on students' problem solving abilities, (3) there were interactions between PBL models, achievement motivation and student problem solving abilities. So that it can be concluded that students who learn with the PBL model have a better ability to solve problems than students who learn with a discussion model. Students with high achievement motivation have better problem solving skills than students with low achievement motivation. The final conclusion is that students' problem solving abilities can be achieved well if they pay attention to both variables at once, namely the model and achievement motivation.